STUDY THE REALITY OF THE PARK BETWEEN THE TWO BRIDGES IN BAQUBA CITY (MABAIN ALJESRAIN) - Jasim, Sada Neseef; Al-Hayany, Ali Mohammed; Zaman, Miasar RiadH (Diyala Agricultural Sciences Journal, 2018)
The urban parks are considered one of the important usage for land within the urban space of the city, as it has even become one of the basic components with the increasing needs of the population as it is being one of the spaces that combine the activities of psychological comfort and pleasure and aesthetic in addition to the environmental, social and health benefits. In order to raise the efficiency of these fields, it's very significant to study the reality of the external spaces and urban parks so as to be able to perform its functions, which are prepared to. In connected with the mentioned before, the necessity to conduct an analytical study of the reality for the park between the two bridges "MABAIN AL JESRAIN PARK" in the city of Baquba. To study the reality of the design and planning of the park has reached search to several conclusions including: that the visit of the male of the park higher than the proportion of females, as it stood at 64.28% and that young people are the most reluctant of the park by 60.00%, and the ease of access of visitors to the park led to a repeat visit by 74.42 % that is due for a briefing to two streets an key location in the city center, which mediates its neighborhoods.